2020
DOI: 10.1007/s11356-020-09275-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of magnetic biochar adsorbents for the removal of Cr(VI) and Acid orange 7 dye from aqueous solution

Abstract: In this study, different types of magnetic biochar nanocomposites were synthesized using the co-precipitation method. Two biochar materials, namely, sewage sludge biochar and woodchips biochar, were prepared at two different temperatures, viz., 450 and 700 °C. These biochars were further modified with magnetic nanoparticles (Fe 3 O 4 ). The modified biochar nanocomposites were characterized using field emission–scanning electron microscopy (FE-SEM), X-ray diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…This was attributed to the presence of iron oxides particles on the biochar surface. The Fe3O4/γ-Fe2O3 particles loaded on the adsorbent surface exhibit magnetic properties, which in turn render the biochar magnetically active (24). Moreover, the magnetization curve suggested that the adsorbent was ferromagnetic, attesting the potential for easy retrievability and reusability through magnetic recovery.…”
Section: Resultsmentioning
confidence: 99%
“…This was attributed to the presence of iron oxides particles on the biochar surface. The Fe3O4/γ-Fe2O3 particles loaded on the adsorbent surface exhibit magnetic properties, which in turn render the biochar magnetically active (24). Moreover, the magnetization curve suggested that the adsorbent was ferromagnetic, attesting the potential for easy retrievability and reusability through magnetic recovery.…”
Section: Resultsmentioning
confidence: 99%
“…The highest pH was obtained for TF and SS samples. Increased pH may imply the presence of inorganic alkaline components in the biochars [59] .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in FT-IR, spectra a peak at 3294 cm -1 shows stretch vibration of bonded hydroxyl groups, and peak at 1643 cm -1 shows the presence of carbonyl group and confirms the carbonaceous nature of the coir. [19,20] found to be increased in 400-450 nm wavelength range with increased pH and decreases within 500-800 nm range with pH attributes the adsorption of MB increases with negative charge of surface of adsorbent. Generally, the net positive charge of adsorbate decreases with increasing pH value, leading to decrease in the repulsion between the adsorbent surface and dye.…”
Section: Physical Characteristics Of Coconut Coirmentioning
confidence: 89%